Togo : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Requests for Waivers of Performance Criteria and Augmentation of Access; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Togo's macroeconomic situation remains difficult, despite some modest improvements. Despite the impact of the global recession, program implementation has generally been satisfactory, although corrective actions are necessary for recent slippages. Debt management and monitoring are being strengthened. In light of the difficult macroeconomic conditions, a countercyclical fiscal policy stance is required. Sustainable fiscal policy requires a gradual consolidation, as global conditions improve further. Togo's main economic challenges are continuing to strengthen public finances and completing structural reforms to enhance growth potential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet